Brain Rot and Youth Morality in the Digital Era: Islamic Perspective on Jombang Students Using CDA-SFL - Chalimah Chalimah; Riyadi Santosa; Djatmika Djatmika; Tri Wiratno; Husniah Ramadhani Pulungan; Jabbar Abdulrahman Qahar; Maaz Ud Din (FITRAH: Jurnal Kajian Ilmu-ilmu Keislaman, 2026)
The rapid expansion of AI has created new learning opportunities; however, excessive reliance on AI may produce negative cognitive and ethical consequences, commonly referred to as “brain rot.” This phenomenon includes reduced critical thinking, dependence on automated responses, plagiarism, and vulnerability to misinformation. Such risks may also undermine core Islamic values, particularly tawhid (monotheism), moral responsibility, and academic integrity. These concerns are especially critical for students whose cognitive and moral development is still forming. This study explores the impact of excessive AI by examining how brain-rot symptoms appear in students’ language and attitudes. Using a qualitative design, the study applies CDA integrated with an SFL approach to analyze students’ questionnaire responses as the primary data source. The research was conducted in Jombang, East Java, a region widely known as a religious and educational center. The findings reveal two discourse patterns related to brain-rot symptoms. The first pattern reflects critical awareness of excessive AI, indicated by 21 linguistic and behavioral indicators showing resistance to overreliance on AI. The second pattern reflects support for excessive AI, indicated by 8 indicators showing perceived positive impacts of AI dependence. These patterns demonstrate varying levels of students’ cognitive dependence on AI. This study proposes a linguistic framework for identifying brain-rot symptoms in educational discourse and provides empirical evidence linking excessive AI use with risks to academic integrity and Islamic moral values. The findings highlight the need for educators, policymakers, and religious institutions to promote responsible and balanced AI use in education, particularly for adolescents